(untitled) (Bangladesh Journal of Zoology, 2022)
Dry fish is considered as a delicacy in the menu of many people of Bangladesh. The most economically important marine and freshwater dried fishes are ribbon fish, bombay duck, olive barb, pomfret, shrimp, etc. In this study, fresh ribbon fish sample was collected from Cox’s Bazar and morphologically identified as ribbon fish. The collected fish was confirmed through a molecular technique using mitochondrial COI gene (cytochrome c oxidase subunit I) to avoid morphological ambiguity, which is first reported data from Bangladesh. Partial sequence of this COI gene was amplified using a genus specific universal primer set. The target nucleotide sequence of COI gene was determined successfully with 616 bp length and the ribbon fish was identified as Eupleurogrammus sp. Within the amplified region GC and AT content were 45.5% and 54.5%, respectively. 16.88% interspecific polymorphism was observed when compared with other species under genus Eupleurogrammus collected from Gen Bank database. This sequence will be used as molecular bar code for authentic identification of Eupleurogrammus sp. at genus level. Bangladesh J. Zool. 50 (2): 231-238, 2022